A abordagem integrada da termorregulação no ensino de Biologia na educação básica - Camilo de Lelis Moraes (2020)
Thermoregulation is a rhythmic and seasonal phenomenon typical of living beings, and is currently incorporated into Chronobiology, a science that investigates the temporal organization of biological rhythms. It is a subject that appears commonly implicit in the contents and classes of Biology. A better understanding of thermoregulation can allow students to conceptualize the meanings of homeostasis and metabolism, important terms in learning in Biology. The main objective of this work was to build na investigative didactic sequence, capable of contributing to the teaching-learning in thermoregulation, in a differentiated and integrated way. The didactic sequence was applied to 30 students in the 2nd / 3rd year of high school at a public school in the town of Entre Rios de Minas. The application occurred in stages, where students were initially encouraged to socialize their previous knowledge, through a discussion mediated by the teacher and the application of a diagnostic questionnaire. Subsequently, the construction of hypotheses and the execution of a practical activity occurred, which favored an increase in student leadership during the learning process. In the experimental stage, the students made measurements of body temperature of their colleagues, the data being recorded, analyzed and compared with the discussions and hypotheses raised by them. The development of this work enabled significant learning and developed the students' argumentative capacity. The construction of knowledge by students made it possible to discuss how scientific concepts are developed and also contribute to health promotion, as a collective and educational action.